2008
DOI: 10.1039/b812698d
|View full text |Cite
|
Sign up to set email alerts
|

A modular and organocatalytic approach to γ-butyrolactone autoregulators from Streptomycetes

Abstract: A general synthesis of optically active gamma-butyrolactone autoregulators is developed by a two-step sequence to assemble 2,3-trans-disubstituted butyrolactones in high yields and enantioselectivities; the scope of this reaction was elaborated by setting up a library of alkyl-substituted butyrolactones and the synthesis of the autoregulators IM-2 and VB-D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Repeated runs using recycled hybrid solid as catalyst. 50 Table 2 shows that the catalytic performance of the hybrid solid remained unchanged throughout the three first runs and catalyst deactivation occurs at run 4, probably due to organocatalyst degradation and/or leaching after successive submission of the solid material to the thermal conditions used in the reaction (see 55 ESI for details).…”
Section: -45mentioning
confidence: 99%
See 3 more Smart Citations
“…Repeated runs using recycled hybrid solid as catalyst. 50 Table 2 shows that the catalytic performance of the hybrid solid remained unchanged throughout the three first runs and catalyst deactivation occurs at run 4, probably due to organocatalyst degradation and/or leaching after successive submission of the solid material to the thermal conditions used in the reaction (see 55 ESI for details).…”
Section: -45mentioning
confidence: 99%
“…Furthermore, combination of the homogeneous catalyst with 4 ÅMS or Silica 100 under otherwise similar conditions also furnishes the desired product in very low yield. The distinctive 50 reactivity offered by the hybrid catalyst could be attributed to the presence of the aminopropyl groups on the solid material. The primary amine sites would react with the aldehyde to form an imine intermediate, more prone to be attacked (when compared to 60 the starting aldehyde) by the deprotonated nitromethane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, Jørgensen et al reported on the Michael addition to functionalized nitroolefins for the synthesis of g-butyrolactone autoregulators, secondary metabolites of the Streptomyces species (Scheme 11.36). 70 The key stereogenic center of this family of butyrolactone was achieved via the cinchona derivative 148 catalyzed addition of suitable carbonyl donor containing an oxazolidinone such as 146. This moiety can easily be converted into the lactone by O-silyl deprotection-cyclization, affording the trans-ring junction.…”
Section: Synthesis Of 144mentioning
confidence: 99%